KAJIAN RENCANA ANGGARAN BIAYA (RAB) UNTUK NORMALISASI SUNGAI MENDOL KECAMATAN KUALA KAMPAR KABUPATEN PELALAWAN - Nurdin -; Imam Suprayogi; Bochari - (Jurnal APTEK, 2012)
The aim of this research was analyze cost estimation budgeting for river normalization of length 6 kms atau 6000 m from River Mouth of Mendol, Kuala Kampar Residence, Pelalawan District, Riau Province. Method was used used to analyze bad level design of Mendol River using Linearly Method Software’s Excel 7.0. The result of this research prove that bad level design of Mendol River from upstream to downstream (river mouth) is 0.07% and cost estimation budgeting is Rp.614.841.965.